[RETRACTED] Eco-centric Theory: Environmental Conscious Constitution - Hasibuan, Rangga Hotman (Administrative and Environtmental Law Review, 2024)
Many national constitutions incorporate elements of environmental constitutionalism, yet the absence of these provisions in some countries indicates suboptimal implementation. This normative juridical research investigated the key factors that influence a country's decision to embrace environmental constitutionalism based on historical case studies of countries that have amended their constitutions in this area, underscoring the contextual background as a pivotal influence on the constitutional amendment process. This environment inevitably shaped the amendment process, exposing it to a variety of influential factors. The research concluded by emphasizing critical strategies necessary for successful constitutional amendments, including aligning environmental protection with national values, leveraging crises, addressing economic factors thoroughly, and garnering the requisite political support from both the public and politicians.